Analysis of atmospheric volatile impurities in the Antarctic glacier content, Galindez Island, Vernadsky - V. I. Bogillo; R. Borchers; M. S. Bazylevska (Ukrainian Antarctic Journal, 2004)
The procedure of extraction, cryogenic concentration and GC MS analysis of atmospheric volatile impurities in content of the retreated coastal Antarctic glacier (Galindez Island, station “Vernadsky”) has been developed. The results on content and changing the concentrations of highly volatile compounds involved in modern and ancient layers of the glacier have been discussed. These data confirm anthropogenic origin of chlorofluorocarbons, their replacements and methylchloroform in Earth’ atmosphere, whereas the observed CF4, N2O, CO2, C3H6, CH3Cl, C2H5Cl, CH2=CHCl, CH3Br, CH2Br2, CHBr3, CH3I, CH2=CHI, C2H5I, COS, CS2, CH3SCH3 and CH3SSCH3 have the natural sources.